Development of a new real-time PCR for the detection of pilchard orthomyxovirus (POMV) in apparently healthy fish - Samsing, Francisca; Tengesdal, Hedda Kjølleberg; Nylund, Are; Rigby, Megan; Wiltshire, Kathryn H.; Morrison, Richard N.; Godwin, Scott; Giles, Carla; Wilson, Teresa; Mohr, Peter G.; Hoad, John; Wynne, James W. (Aquaculture, 2022)
Pilchard orthomyxovirus (POMV) is a virus of concern to the Atlantic salmon aquaculture industry in Tasmania. First isolated from wild pilchards in southern Australia in 1998, the virus is now a recognised pathogen of farmed Atlantic salmon (Salmo salar) in Tasmania. While the current real-time PCR for POMV targets segment 5 of the viral genome, recent viral gene expression data suggests that other segments of the POMV genome presented higher transcription levels and thus may be better candidates for the early detection of the virus. This study aimed to design and begin validating a more sensitive reverse transcriptase real-time PCR (RT-qPCR) assay to detect POMV. Primers and probes were developed targeting two independent viral genes derived from segments 7 and 8, which presented higher transcription levels than segment 5 in both cell culture and infected fish. These were compared with the current POMV RT-qPCR. The POMV segment 8 assay had a higher analytical sensitivity than segment 7, detecting at least 1 plasmid copy μl−1, and was 10-fold more sensitive than both POMV segment 7 and 5 assays when analysing nucleic acid from a positive field sample. Both new assays also had high analytical specificity, detecting the 11 POMV isolates tested (inclusivity testing) and not amplifying nucleic acids from other viruses, including ISAV, a related orthomyxovirus. In the latent class model analysis, the diagnostic sensitivity of the segment 8 and 7 assays were higher than segment 5 in 93% and 92% of simulations, respectively. Seven samples (18.4%), all from subclinical fish infected with POMV, returned a positive result only with the segment 8 assay. Both new assays showed reproducible results when applied to aliquots of the same samples tested in three different laboratories. The new POMV segment 8 assay shows promising results as a surveillance tool for detecting POMV in fish without any symptoms. publishedVersion